A transcendência como mecanismo de filtragem para o recurso de revista - Albuquerque, Leonidas Cabral (2014)
The research about transcendence, as a method of selection of recursos de revista in labor process, starts with the study of the writ of error and the writ of certiorari in Supreme Court of United States, influencing the brazilian procedural system, initially the recurso extraordinário designed in the establishment of Republic, the claim of relevance in the previous constitutional order and, modernly, in the institute of repercussão geral on the recurso extraordinário to the Supremo Tribunal Federal. These are experiences which are indispensable to the formation of a more solid ground so that the transcendence criterion is properly conducted in the Tribunal Superior do Trabalho, by the lawyers whose cases are brought, through the recurso de revista, to the attention of this Court. The analysis resorting the dialetic method is contextualized in the brazilian historic and social evolution, as well as in the changes of procedural legislation, which were motivated by the celerity and effectiveness of the adjudication. Transcendence comes as a remedy for the Tribunal Superior do Trabalho crisis, allowing the replacement of decision in each case by the judgment of causes seen as relevant and representative of the issues that most occupy and concern the litigants and the labor jurisdiction, in order to fulfill its mission of standardizing the labor laws interpretation and enforcement across the country. Besides the study of the relevant procedural law, there will be an exam of proposed rulemaking of transcendence. In the conclusion are listed some contributions to the doctrinal debate and propositions to the regulation which is still under examination at the Tribunal Superior do Trabalho